1947
DOI: 10.2307/1493
|View full text |Cite
|
Sign up to set email alerts
|

The Natural Control of Population Balance in the Knapweed Gall-Fly (Urophora jaceana)

Abstract: All use subject to JSTOR Terms and Conditions * Until I937 the knapweed gall-fly was known in this country as Urophora solstitialis (L.), but it had long been known that continental U. solstitialis was usually a gall-fly of thistles. However, gall-flies bred from the continental knapweed Centaurea jacea were found to differ from the thistle species, and were described as new by Hering (I935) under the name jaceana. Collin (1937) has found that the British specimens from knapweed are in fact jaceana, and not so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
3

Year Published

1961
1961
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(82 citation statements)
references
References 18 publications
3
76
0
3
Order By: Relevance
“…E. robusta has a broad host range, unlike the monophagous parasitoid E. serratulae, and its oviposition period is often not well synchronized with the gall development of U. cardui (Zwölfer et al, in prep. ), as previously reported by Varley (1947) for an E. robusta population attacking galls of Urophora jaceana Hering in knapweed flower heads. E. robusta females prefer U. cardui galls containing thirdinstar larvae, but are unable to assess the optimal U. cardui gall sizes for oviposition (Zwölfer et al, in prep.…”
Section: Discussionsupporting
confidence: 84%
“…E. robusta has a broad host range, unlike the monophagous parasitoid E. serratulae, and its oviposition period is often not well synchronized with the gall development of U. cardui (Zwölfer et al, in prep. ), as previously reported by Varley (1947) for an E. robusta population attacking galls of Urophora jaceana Hering in knapweed flower heads. E. robusta females prefer U. cardui galls containing thirdinstar larvae, but are unable to assess the optimal U. cardui gall sizes for oviposition (Zwölfer et al, in prep.…”
Section: Discussionsupporting
confidence: 84%
“…described here, suggested by Professor G. C. VarThe population dynamics of oak-feeding Lepi-ley, provides evidence in favor of this hypothesis. doptera in Wytham Wood have been studied for several years by Varley andGradwell (1958a, 1963b). They conclude that the fluctuations in density from year to year, largely synchronous for all early-feeding species, are determined by the density-independent action of weather, but that the relative population levels of the different species are largely governed by differing efficiencies of the specific parasites, acting in a delayed densitydependent manner (Varley 1947).…”
Section: Introductionmentioning
confidence: 99%
“…doptera in Wytham Wood have been studied for several years by Varley andGradwell (1958a, 1963b). They conclude that the fluctuations in density from year to year, largely synchronous for all early-feeding species, are determined by the density-independent action of weather, but that the relative population levels of the different species are largely governed by differing efficiencies of the specific parasites, acting in a delayed densitydependent manner (Varley 1947). While parasitism may be sufficient to control at low level the less common Lepidoptera species, which seem to suffer from more efficient parasites, parasitism of the more abundant species is unable to prevent the host density from occasionally reaching the food limit.…”
Section: Introductionmentioning
confidence: 99%
“…(c) Populations controlled by interaction with predator or parasite populations (a view supported by observations on insect populations, e.g., Varley (1947». A classic demonstration that predators may control the balance of species in a plant community is found in the experiments of Jones (1933) who showed that various agriculturally desirable and undesirable combinations of species could be created from an initial mixed population by controlling the time and intensity of grazing by a predator (the sheep). Many comparable examples can be found in the agricultural literature, but studies on natural vegetation are extremely rare, badly documented, or derive from uncontrolled experiments.…”
Section: The Ecologic Problemsmentioning
confidence: 98%